An ortholog of LEAFY in Jatropha curcas regulates flowering time and floral organ development - Tang, Mingyong (Sci Rep, 2016)
Jatropha curcas seeds are an excellent biofuel feedstock, but seed yields of Jatropha are limited by its poor flowering and fruiting ability. Thus, identifying genes controlling flowering is critical for genetic improvement of seed yield. We isolated the JcLFY, a Jatropha ortholog of Arabidopsis thaliana LEAFY (LFY), and identified JcLFY function by overexpressing it in Arabidopsis and Jatropha. JcLFY is expressed in Jatropha inflorescence buds, flower buds, and carpels, with highest expression in the early developmental stage of flower buds. JcLFY overexpression induced early flowering, solitary flowers, and terminal flowers in Arabidopsis, and also rescued the delayed flowering phenotype of lfy-15, a LFY loss-of-function Arabidopsis mutant. Microarray and qPCR analysis revealed several flower identity and flower organ development genes were upregulated in JcLFY-overexpressing Arabidopsis. JcLFY overexpression in Jatropha also induced early flowering. Significant changes in inflorescence structure, floral organs, and fruit shape occurred in JcLFY co-suppressed plants in which expression of several flower identity and floral organ development genes were changed. This suggests JcLFY is involved in regulating flower identity, floral organ patterns, and fruit shape, although JcLFY function in Jatropha floral meristem determination is not as strong as that of Arabidopsis.